The impact of delivery daytime and seasonality of radiotherapy for head and neck cancer on toxicity burden. (May 2021) - Brolese, Eliane Koller; Cihoric, Nikola; Bojaxhiu, Beat; Sermaxhaj, Burim; Schanne, Daniel Hendrik; Mathier, Etienne; Lippmann, Jana; Shelan, Mohamed; Eller, Yannick; Aebersold, Daniel M.; Giger, Roland; Elicin, Olgun
Highlights: Circadian rhythm was previously shown to correlate with treatment toxicity. Such findings could not be reproduced in this institutional cohort. This is the first study investigating the impact of seasons on treatment toxicity. Radiotherapy delivery in the darker half of the year yielded higher acute toxicity. Abstract: Aim: The potential impact of the daytime and season of radiotherapy application on acute and late toxicity burden was analyzed on a cohort of curatively treated head and neck squamous cell carcinoma patients. Methods: Through a retrospective chart review, patient and tumor characteristics, treatment parameters and outcome were obtained. Patients treated with definitive or adjuvant radiotherapy with and without chemotherapy receiving ≥60 Gy between 2002 and 2015 were included ( n = 617). Daily fraction times and dates were extracted. Median radiotherapy delivery time of each patient was categorized as morning (AM) and afternoon (PM). Treatment season was defined by the median day of the treatment course. Each year was divided into DARK and LIGHT by the March and September equinoxes. Acute (T) and late (A) toxicity were defined by TAME methodology. Results: Median follow-up was 51 months. Mean T and A scores during and after radiotherapy in DARK vs. LIGHT were 1.98 vs. 1.61 ( p = 0.0127) and 0.41 vs. 0.30 ( p = 0.1699), respectively. Mean T and A scores during and after AM vs. PM radiotherapy were 1.71 vs. 1.88 ( p = 0.0387) and 0.31 vs. 0.41 ( p = 0.2638), respectively. Multivariate analyses indicated DARK vs. LIGHT as the only independent treatment time-related factor among other factors such as tumor subsite, UICC stage, radiotherapy technique, and chemotherapy for T. Conclusion: This is the first study investigating the impact of seasonality on toxicity burden, showing higher acute toxicity with radiotherapy in DARK. The daytime did not predict the toxicity. The hypothesis-generating findings of this retrospective study should be further investigated.